Representations in the learning of Sequences and Regularities by 3rd grade Students - Faria, Ana Raquel; Viseu, Floriano; Gomes, Alexandra; Aires, Ana Paula (International Electronic Journal of Elementary Education, 2022)
The abstract nature of mathematical concepts makes that their representation through different registers favours their understanding. In the case of 'Sequences and Regularities', it becomes propitious the exploration of different registers of representation in the institution of topics, such as term, order, formation law and generating expression. Considering these assumptions, a teaching experiment was carried out in order to understand the contribution of multiple representations in the learning of 'Sequences and Regularities' by 3rd grade students. Adopting a qualitative methodology, the study shows that students initially presented a smaller variety of representations, which increased during the teaching experience. Students revealed a greater preference for pictorial representations and made explicit connections between different representations throughout their resolutions. Pictorial representations and tables allowed close and distant generalizations, the determination of the formation law and the generating expression. The greatest difficulties of the students resulted from the interpretation of the statements of the proposed tasks, that was also evident in the representation (natural language), which revealed a greater number of incorrect answers. This result tends to reveal that some students still have difficulties in justifying their reasoning, either in writing or orally.